2017
DOI: 10.3171/2016.2.jns1633
|View full text |Cite
|
Sign up to set email alerts
|

BRAF V600E mutation and BRAF kinase inhibitors in conjunction with stereotactic radiosurgery for intracranial melanoma metastases

Abstract: OBJECTIVE Recent advancements in molecular biology have identified the BRAF mutation as a common mutation in melanoma. The wide use of BRAF kinase inhibitor ( BRAFi) in patients with metastatic melanoma has been established. The objective of this study was to examine the impact of BRAF mutation status and use of BRAFi in conjunction with stereotactic radiosurgery (SRS). METHODS This was a single-center retrospective study. Patient's charts and electronic records were reviewed for date of diagnosis of primary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…Although initial studies of BRAFi alone in the setting of BM42,45 reported minimal intracranial toxicity, including hemorrhage, Lee et al67 noted the development of ICH in a patient treated with Cyberknife radiosurgery in combination with DAB and the MEKi TRA. Although Xu et al59 did note an increased rate of ICH in BRAF-mutated patients treated with BRAFi and radiation versus BRAF-mutated patients treated with radiotherapy alone (29.4% vs 8.6%), the results were not significant ( P =0.487). In contrast, Ly et al57 reported a significantly increased risk of hemorrhage in BRAF-mutated patients treated with BRAFi and radiation.…”
Section: Toxicity Of Intracranial Radiation In Conjunction With Brafismentioning
confidence: 82%
See 2 more Smart Citations
“…Although initial studies of BRAFi alone in the setting of BM42,45 reported minimal intracranial toxicity, including hemorrhage, Lee et al67 noted the development of ICH in a patient treated with Cyberknife radiosurgery in combination with DAB and the MEKi TRA. Although Xu et al59 did note an increased rate of ICH in BRAF-mutated patients treated with BRAFi and radiation versus BRAF-mutated patients treated with radiotherapy alone (29.4% vs 8.6%), the results were not significant ( P =0.487). In contrast, Ly et al57 reported a significantly increased risk of hemorrhage in BRAF-mutated patients treated with BRAFi and radiation.…”
Section: Toxicity Of Intracranial Radiation In Conjunction With Brafismentioning
confidence: 82%
“…Gaudy-Marqueste et al55 and Patel et al60 reported 0% radiographic or symptomatic RN, while Narayana et al54 and Ahmed et al56 both reported very low rates of RN, 8.3% and 4.2%, respectively. Xu et al59 found no difference in the development of RN between BRAF-mutated patients treated with BRAFi and GKRS versus BRAF-mutated patients treated with GKRS alone (17.6% vs 8.6%, P =0.721). In contrast, Patel et al58 found a statistically significant difference in symptomatic RN between SRS and BRAFi and SRS alone cohorts (28.2% vs 11.1%, P <0.001).…”
Section: Toxicity Of Intracranial Radiation In Conjunction With Brafismentioning
confidence: 96%
See 1 more Smart Citation
“…107 The multicenter, open-label, phase II BREAK-MB trial enrolled 172 patients with asymptomatic, untreated (cohort A) or progressive (cohort B) brain metastases in melanoma patients with V600E or V600K mutation for treatment with dabrafenib (class IIb). 108 Over 80% of patients in both cohorts with V600E mutations had intracranial disease control (CR+PR+SD), median PFS was longer than 16 weeks in both cohorts, and OS exceeded 31 weeks.The combination of BRAF inhibitors and SRS could improve survival, 109,110 but an increase of toxicities Table 3 Recommendations regarding treatment of newly diagnosed brain metastases…”
Section: Neurooncologymentioning
confidence: 99%
“…Due to the minimum skin dose from SRS, several studies that evaluated BRAF inhibitor with SRS for patients with brain metastases reported favorable outcome (137)(138)(139). Studies that directly compared outcomes of patients treated with SRS alone and SRS with BRAF inhibitor suggest that there indeed may be a survival benefit of combination therapy (140)(141)(142). However, it seems that because of the radiosensitization effect, increased toxicity other than skin toxicity may also be induced, such as radionecrosis (141).…”
Section: Rt With Concomitant Agentsmentioning
confidence: 98%